Association of serum irisin with gestational diabetes mellitus - Sultana, Abeda; Joarder, M. Akhtanur Rahman; Begum, Khadiza; Shamsunnahar, Nafisa; Ferdous, Sharmin; Parveen, Tabassum (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Gestational diabetes mellitus (GDM) is a condition characterized by glucose intolerance with onset during pregnancy, increasing risks to both mother and child. Recent studies have focused on irisin, a hormone linked to energy metabolism and insulin sensitivity, to understand its role in GDM. This study aimed to explore the relationship between serum irisin levels and the incidence of GDM. Methods: This prospective diagnostic accuracy study was conducted at the outpatient Department of Fetomaternal Medicine and the Department of Obstetrics and Gynecology at BSMMU in Dhaka from July 2021 to June 2022. According to the inclusion criteria, 65 pregnant women who were non-GDM at 11-14 weeks were selected purposively. Serum irisin levels were measured in these non-diabetic participants using an enzyme-linked immunosorbent assay (ELISA) kit. The participants were divided into two groups: those with reduced irisin levels and those with normal irisin levels. Data were then analyzed using statistical package for the social sciences (SPSS) version 23.0 software. Results: Among the low irisin group, 36.4% were diagnosed with GDM, while 63.6% remained euglycemic. In the high irisin group, 97.7% remained euglycemic, and 2.3% developed GDM. Overall, 14% of respondents were with GDM across both groups. The ROC analysis for detecting GDM based on irisin levels showed statistically significant results with an AUC of 0.834. A cut-off value of ≤0.287 had 88.9% sensitivity and 75% specificity, leading to 76.9% accuracy. The PPV was 36.4%, and the NPV was 97.7%. The mean serum irisin level was significantly lower in mothers with GDM compared to non-GDM mothers (p=0.001). Conclusions: The maternal serum irisin level is found to be lower in pregnant women with GDM compared to those without GDM. Therefore, in pregnancy, maternal serum irisin levels may be useful as a biomarker for detection of GDM.